Normative Analysis of The Prohibition on The Sale and Purchase of Ownership Certificates in Kampung Tua, Batam City by The Batam City Government and The Batam City National Land Agency - Nur Sidhi, Mas Imam; Riyanto, Taufan Fajar; Dwi Istinah, Siti Rodhiyah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This thesis research aims to analyze in detailsocialThe prohibition on the sale and purchase of Land Ownership Certificates (SHM) in the Kampung Tua area of Batam City, as stipulated in Batam Mayor Regulation Number 2 of 2024 and its implementation by the National Land Agency (BPN) of Batam City. This study uses a juridical research method.socialve with a statute approach, a conceptual approach, and a case/policy approach. The legal sources used include primary legal materials in the form of the Basic Agrarian Law, Batam Mayor Regulation Number 2 of 2024, and related land regulations; secondary legal materials in the form of books, scientific journals, and previous research results; and tertiary legal materials such as legal dictionaries and encyclopedias. The legal material collection technique is carried out through literature studies and document studies, while the analysis is carried out qualitatively by interpreting legal norms, examining the hierarchy of laws and regulations, and assessing the suitability of policies with the principles of land law such as legal certainty, justice, benefit, and protection of rights. The results of the study indicate that in generalsocialThe validity of the policy prohibiting the sale and purchase of SHM in Kampung Tua still raises legal issues because it has the potential for disharmony with the provisions of the Basic Agrarian Law (UUPA), which guarantees property rights as the strongest and most complete transferable rights. The implementation of the ban by the Batam National Land Agency (BPN) has legal consequences in the form of restrictions on the transfer of rights and delays in land services, as well as impacting aspectssocial issues such as declining legal certainty, the economic value of land, and the potential for community conflict. However, this policy also aims to protect the sustainability of Kampung Tua, necessitating synchronized regulations and equitable policy formulation.